2009
DOI: 10.1515/bc.2009.037
|View full text |Cite
|
Sign up to set email alerts
|

Structure-function relationship of the human antimicrobial peptide LL-37 and LL-37 fragments in the modulation of TLR responses

Abstract: Cathelicidins are effector molecules of the innate host defense system that establish an antimicrobial barrier at epithelial interfaces. The human cathelicidin LL-37, in addition to its antimicrobial activity, also exhibits immunomodulatory effects, such as inhibition of pro-inflammatory responses to bacterial LPS in human monocytic cells. In this report, we demonstrate that LL-37 almost completely prevents the pro-inflammatory cytokine release by human peripheral blood mononuclear cells (PBMCs) following stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
72
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 52 publications
9
72
0
Order By: Relevance
“…In line with our observations, Nan et al [12] showed that substitution of Trp by Lys residues in the Trp-rich peptide indolicidin resulted in decreased hydrophobicity and loss of LPS-neutralising activity. Previously it was shown that inhibition of the pro-inflammatory response is mainly established by direct binding of cationic HDPs to LPS [11,13]. In line with these observations, we found a correlation between LPS-neutralising activities and LPS binding.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with our observations, Nan et al [12] showed that substitution of Trp by Lys residues in the Trp-rich peptide indolicidin resulted in decreased hydrophobicity and loss of LPS-neutralising activity. Previously it was shown that inhibition of the pro-inflammatory response is mainly established by direct binding of cationic HDPs to LPS [11,13]. In line with these observations, we found a correlation between LPS-neutralising activities and LPS binding.…”
Section: Discussionsupporting
confidence: 91%
“…PheTrp substitutions in C1-15, resulting in peptide F2,5,12W, significantly increased the LPS-neutralising capacity. Recently, we [11] and others [12] reported the importance of hydrophobicity in neutralising LPS cytokine responses. In line with our observations, Nan et al [12] showed that substitution of Trp by Lys residues in the Trp-rich peptide indolicidin resulted in decreased hydrophobicity and loss of LPS-neutralising activity.…”
Section: Discussionmentioning
confidence: 93%
“…Preliminary experiments revealed that these C-terminal peptides are more effective than LL-37 in killing of Staphylococcus aureus as detected by radial diffusion assays (T. Vos, A. van der Does, B. Ravensbergen, H. Beekhuizen, and P. Nibbering, unpublished results). In agreement, is has been reported that the LL-37-derived peptides covering residues 13-35 are at least as effective as LL-37 with respect to LPS neutralization (31), modulation of TLR-mediated responses (34), and inducing secondary necrosis of apoptotic neutrophils (35). These structure-function studies can be helpful in the design of new candidate peptides for the treatment of infections.…”
Section: Discussionsupporting
confidence: 67%
“…Mouse mast cells deficient in CRAMP, another member of the cathelicidin family, are less able to kill group A Streptococcus (12). In addition, LL-37 can modulate TLR (54) and immune responses. In a recent study, von Köckritz-Blickwede et al (11) demonstrated that the human mast cell line HMC-1 elicited antimicrobial activity that was independent of phagocytosis.…”
Section: Discussionmentioning
confidence: 99%